Organizational and Market Dynamics Associated with Usable, Accessible Health Information Exchange for Skilled Nursing Facilities. (20th August 2020) - Cross, D.; Everson, J.; Patel, V.
Abstract : Information discontinuity between hospitals and skilled nursing facilities (SNFs) is a critical barrier to safe and effective transitions. To engage effectively in information sharing, SNFs need structural health information exchange (HIE) capabilities but also HIE design and workflows that result in electronic information actually being accessible and usable at the point of care. We use nationally representative SNF data to identify key facility characteristics, and characteristics of the facility's top hospital referral partner, that are associated with likelihood of SNFs having access to electronic information sharing tools. Controlling for those capabilities, we then assess the extent to which those same characteristics influence the extent to which the SNF reports usable information received electronically that is actually available at the point of care. We conducted pooled, cross‐sectional survey data analyses. We identified our sample of SNFs through the Office of the National Coordinator SNF Health IT Survey (2016‐2017). From this survey, we generated our SNF HIE capability metric (ability to electronically query for or receive patient information from outside sources) as well as our key study outcome—whether SNFs report usable electronic information from outside sources available at the point of care. Organizational SNF characteristics were pulled from the SK&A Nursing Home datafile as well as the CMS Nursing Home Public Use file. We matched each SNF to the hospital responsible for sending the highest percent of their referrals using Medicare referral pattern data and used these same data to calculate a measure of SNF referral relationship concentration. We then, for each partner hospital, used the American Hospital Association (AHA) IT Supplement to identify general and SNF‐specific HIE capabilities. We use linear probability models to estimate the association between relevant organizational characteristics (of the SNF and partner hospital) and both HIE outcomes: (1) SNF HIE capabilities and (2) SNF self‐reported availability of usable and accessible outside information at the point of care (controlling for HIE capabilities). Nationally representative sample of skilled nursing facilities (N = 1, 189). Controlling for the presence of an EHR, SNFs are more likely to electronically query for or receive information from outside sources if they are large (+10.3%, top tertile compared to bottom; P = .004), if they are part of a large chain (+11.7%, member of 70+ nursing home chain, compared to standalone; P = .001), and if their partnering hospital reports having a health information portal (+7.5%; P = .049). Adjusting for SNF HIE capabilities, SNFs have a higher probability of usable electronic information available at the point of care if their top partner hospital reports participation in a community HIO (+7.6%; P = .018). Hospital information portals increase SNF access to HIE infrastructure, but community‐level HIOs increase the likelihood that SNFs actually have accessible, usable electronic information from hospitals at the point of care. Community HIOs appear to play a critical role in SNFs having usable, timely access to outside sources of health information. HIOs have significant opportunity to bolster their value proposition through greater engagement with SNFs and other postacute providers on supporting their informational needs and transitional care processes with hospitals. Office of the National Coordinator for Health IT.